2020
DOI: 10.21203/rs.3.rs-21525/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hepatic encephalopathy increases the risk of hip fracture: a nationwide cohort study

Abstract: Background: Osteoporotic hip fracture is a common general health problem with a significant impact on human life because it debilitates the patients and largely decreases their quality of life. Early prevention of fractures has become essential in recent decades. This can be achieved by evaluating the related risk factors, as a reference for further intervention. This is especially useful for the vulnerable patient group with comorbidities. Hepatic encephalopathy (HE), a major complication of liver cirrhosis, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Data from the US Nationwide Emergency Department Sample (2009-2012) indicated that patients with cirrhosis who presented to the emergency department (ED) with falls had greater odds of severe injury compared with patients without cirrhosis, including intracranial hemorrhage and pelvic fractures [27]. The presence of HE was significantly associated with severe fall-related injuries in patients with cirrhosis [27], and HE was shown to increase the risk of hip fracture in patients aged > 50 years [28]. Thus, it is apparent that the presence of HE in patients with cirrhosis is associated with hospital readmissions, increased mortality, impaired QOL, and greater fall risk.…”
Section: Hepatic Encephalopathymentioning
confidence: 99%
“…Data from the US Nationwide Emergency Department Sample (2009-2012) indicated that patients with cirrhosis who presented to the emergency department (ED) with falls had greater odds of severe injury compared with patients without cirrhosis, including intracranial hemorrhage and pelvic fractures [27]. The presence of HE was significantly associated with severe fall-related injuries in patients with cirrhosis [27], and HE was shown to increase the risk of hip fracture in patients aged > 50 years [28]. Thus, it is apparent that the presence of HE in patients with cirrhosis is associated with hospital readmissions, increased mortality, impaired QOL, and greater fall risk.…”
Section: Hepatic Encephalopathymentioning
confidence: 99%